Analisis Prosedur Audit Persediaan Dalam Mendeteksi Fraud Pt Abc Oleh Kap Xyz - Anisa Azzuhrup; Aurora Novelita; Siti Aidilya Dwi Nov Syafitri; Nanda Destrianti; Eka Merdekawati (CV. ITTC INDONESIA, 2025)
This study aims to identify and analyze the inventory audit procedures implemented by CPA XYZ on company ABC. Using a qualitative approach, this study focuses on the research objects, namely inventory and inventory recording. The focus of this study is to examine how substantive testing procedures are carried out by CPA XYZ. Furthermore, this study also examines the description of inventory account audit techniques and analyzes how the audit objectives are in line with the inventory audit procedures carried out by CPA XYZ to identify recording errors in inventory. This study uses primary data obtained through interviews with members of the audit team from CPA XYZ. The audit results show that the inventory control system is effective without any material findings that affect the fairness of the financial statements. Therefore, CPA XYZ provides an unqualified opinion on PT ABC's inventory report.